The effect of physician prescribing patterns based on ESC guidelines on morbidity improvement among heart failure patients - Ema Pristi Yunita; Anindhita Dwi Safitri; Ardian Rizal (Pharmaciana, 2021)
Data from Basic Health Research shows the prevalence of heart failure in Indonesia is between 0.1% to 0.3% of the entire Indonesian population. This number is predicted to increase from year to year. Heart failure is a complex syndrome that can cause abnormalities in the structure and function of the heart. Based on the ejection fraction values, there are three types of heart failure, namely HFrEF (EF: < 40%), HFmrEF (EF: 40-49%), and HFpEF (EF: â‰¥ 50%). Considering that the type of heart failure requiring treatment according to ESC guidelines is only HFrEF, however, this study would also evaluate the effect of physician prescribing patterns on the morbidity of HFmrEF. The recommendations from ESC guidelines to the treatment of HFrEF that can reduce morbidity and mortality are three medication combinations, namely ACE inhibitors/angiotensin receptor blockers, beta-blockers, and aldosterone antagonists. Therefore, this study aims to determine the effect of the suitability of physician prescribing patterns according to ESC guidelines on improving the morbidity of heart failure patients in HFrEF and HFmrEF type. Improvements in morbidity can be seen from the quality of life score and frequency of hospitalization by using questionnaires. The study was conducted in the cardiology outpatient clinic of Dr. Saiful Anwar General Hospital and Islamic Hospital of Aisyiyah in April-May 2019. Subjects who participated in the study were 57 patients. The One-way ANOVA test results showed no significant difference between physician prescribing patterns of quality of life scores on HFrEF (p = 0.944) while the Kruskal Wallis test for the same parameters on HFmrEF also showed insignificant results (p = 0.210). The Kruskal Wallis test results showed no significant difference between the patterns of physician prescribing to the frequency of hospitalization in both HFrEF and HFmrEF (p = 0.260; p = 0.428). The results showed that physician prescribing patterns in accordance with ESC guidelines resulted in the best quality of life scores on HFrEF. The lowest frequency of hospitalization was also shown in HFrEF patients who received treatment according to ESC guidelines.